Preliminary insight on diarylpentanoids as potential antimalarials: In silico, in vitro pLDH and in vivo zebrafish toxicity assessment - Ramli, Amirah Hani; Swain, Puspanjali; Mohd Fahmi, Muhammad Syafiq Akmal; Abas, Faridah; Leong, Sze Wei; Tejo, Bimo Ario; Shaari, Khozirah; Ali, Amatul Hamizah; Agustar, Hani Kartini; Awang, Rusdam; Ng, Yee Ling; Lau, Yee Ling; et al. (Elsevier, 2024)
Malaria remains a major public health problem worldwide, including in Southeast Asia. Chemotherapeutic agents such as chloroquine (CQ) are effective, but problems with drug resistance and toxicity have necessitated a continuous search for new effective antimalarial agents. Here we report on a virtual screening of ∼300 diarylpentanoids and derivatives, in search of potential Plasmodium falciparum lactate dehydrogenase (PfLDH) inhibitors with acceptable drug-like properties. Several molecules with binding affinities comparable to CQ were chosen for in vitro validation of antimalarial efficacy. Among them, MS33A, MS33C and MS34C are the most promising against CQ-sensitive (3D7) with EC50 values of 1.6, 2.5 and 3.1 μM, respectively. Meanwhile, MS87 (EC50 of 1.85 μM) shown the most active against the CQ-resistant Gombak A strain, and MS33A and MS33C the most effective P. knowlesi inhibitors (EC50 of 3.6 and 5.1 μM, respectively). The in vitro cytotoxicity of selected diarylpentanoids (MS33A, MS33C, MS34C and MS87) was tested on Vero mammalian cells to evaluate parasite selectivity (SI), showing moderate to low cytotoxicity (CC50 > 82 μM). In addition, MS87 exhibited a high SI and the lowest resistance index (RI), suggesting that MS87 may exert effective parasite inhibition with low resistance potential in the CQ-resistant P. falciparum strain. Furthermore, the in vivo toxicity of the molecules on early embryonic development, the cardiovascular system, heart rate, motor activity and apoptosis were assessed in a zebrafish animal model. The overall results indicate the preliminary potential of diarylpentanoids, which need further investigation for their development as new antimalarial agents. © 2024 The Authors